Titel prent: De Oppermachtige : "Laat ze maar schrijven en protesteeren. Niemand in Nederland maakt mij wat!" - Hahn, Albert,
Titel prent: De Oppermachtige : "Laat ze maar schrijven en protesteeren. Niemand in Nederland maakt mij wat!".